Unlocking Energy Sector Reforms: Tackling Monopolies and Regulatory Challenges: Mengatasi Monopoli Alami dan Tantangan Regulasi: Membuka Potensi Reformasi Sektor Energi - Samiev Shakhrukh (Academia Open, 2023)
This article presents a comprehensive examination of recent energy sector reforms, their outcomes, persistent issues related to natural monopolies, regulatory and managerial challenges, and provides suggestions for addressing them. The study aims to analyze the effects of energy sector reforms, identify existing issues, and propose solutions to mitigate them. Using qualitative analysis of literature and data from diverse sources, the study reveals that reforms have fostered increased competition and investment, yet the presence of natural monopolies continues to impede the electricity market's functioning. Regulatory and management challenges, including inadequate frameworks, lack of transparency, and ineffective supervision, are also identified. The implications of this research highlight the need for policymakers to prioritize promoting competition and market-driven mechanisms, implementing effective regulations, and enhancing transparency and accountability in the management of the energy sector. These findings offer valuable insights to researchers, policymakers, and stakeholders globally, facilitating the design and implementation of more effective energy reforms for sustainable development. Highlights: Energy sector reforms: This study examines the effects of recent energy sector reforms, analyzing their impact on competition and investment in the industry. Natural monopolies: Despite reforms, the presence of natural monopolies continues to hinder the functioning of the electricity market, limiting competition and efficiency. Regulatory challenges: Inadequate regulatory frameworks, lack of transparency, and ineffective supervision pose significant obstacles to the successful implementation of energy sector reforms. Keywords: energy sector reforms, natural monopolies, regulatory challenges, competition, transparency.